Android Application Model of "Suami Siaga Plus" as an Innovation in Birth Preparedness and Complication Readiness (BP/CR) Intervention - Hanna Yuanita Dana Santoso; Supriyana Supriyana; Bahiyatun Bahiyatun; Melyana Nurul Widyawati; Diyah Fatmasari; Sudiyono Sudiyono; Dyah Anantalia Widyastari; Doni Marisi Sinaga (Tehran University of Medical Sciences, 2017)
Objective: WHO recommends Mobile health, a practice of medicine and public health supported by mobile devices, to improve community health status and change people's behavior for the health purposes. The present study sought to examine the effectiveness of the android application program of Suami Siaga Plus in increasing husband's scores in birth preparedness and complication readiness (BP/CR) intervention. Materials and methods: It was a randomized controlled trial with pretest-posttest design. A total of 38 couples of husbands and pregnant women from three health centers at three sub districts in Semarang was selected by proportional systematic random sampling technique and equally distributed into control and intervention group. A questionnaire related to BP/CR published by JHPIEGO was employed in data collection. Statistical analysis was performed to obtain the frequency distribution and percentage of the variables, and also to assess the mean difference of BP/CR score of husbands. Results: Husbands' knowledge of key danger signs and five standard elements in BP/CR practices in both intervention and control group increased after counseling. Moreover, the proportion of husbands who understand the key danger signs during pregnancy was higher among those who were exposed by Suami Siaga Plus application delivered via mobile phone. Counseling only increased husbands' score from 61.5 to 62.6 (2%), whilst the combination of counseling and the application boosted 20% of husbands' score from 60.4 to 72.9 (p-value 0.000). Conclusion: A combination of counseling and Suami Siaga Plus application significantly improves husbands and wives' score on BP/CR compared to those who received counseling only. The data suggests the application would be able to suppress the three delays, which in turn can reduce the maternal mortality rate. The study results could be important information for the Department of Health and health professionals to use android application program, in particular to the husband whose wife is in pregnancy, childbirth and postpartum periods.